A Workshop Example of Basic Design Education in Interior Architecture - Hatice Sena Azkur; Murat Oral (Turkish Journal of Agriculture: Food Science and Technology)
The “Basic Design” is one of the common introductory courses in design disciplines. It has great importance in interior architecture education as it forms the basis of design practice. Education that proceeds through abstract concepts creates difficulties for students to internalize this course. To avoid these difficulties, learning by doing is of great importance. The learning-by-doing approach was carried out in the form of a workshop within the scope of the “Basic Design 1” course of the Department of Interior Architecture at Konya Technical University in the fall semester of the 2022-2023 academic year. Students were asked to produce three-dimensional designs using basic design principles and elements. The class was divided into groups of eight people and studies were carried out with a workshop coordinator in each group. The duration of the workshop was planned as four weeks. During the workshop, students learned to use materials and colors, to design an original composition. At the end of the workshop, students learned to embody the abstract concepts they learned during the year by creating a composition that considers functionality and aesthetics. In order to evaluate the efficiency of the workshop, a survey study was carried out after the course period ended. As a result, it has been seen that the intelligibility of Basic Design 1, which is a course taught through abstract concepts, has increased thanks to the workshop.